Daya Dukung Pengembangan Sapi Bali di Kawasan Sentra Perbibitan Sapi Bali Kabupaten Konawe Selatan - Musram Abadi; La Ode Nafiu; Takdir Saili; Lukman Yunus; Abdul Rizal (Faculty of Agriculture, Musamus University, 2022)
This study aimed to determine the carrying capacity of Bali cattle development in the Bali cattle breeding centre in the South Konawe Regency. The location determination was determined by purposive sampling with the consideration that this area is the centre of Bali cattle breeding in Indonesia. The variables that will be seen are the characteristics of the respondents and the carrying capacity of Bali cattle development, the carrying capacity of Bali cattle development based on Location Quotient (LQ) analysis. The results of this study indicate that natural resources are supporting the development of the Bali cattle business in the breeding centre area which includes a total population of 18,842 heads (27%) of the total population, has the potential as a basis for livestock development with an LQ value of 1.1.